Reformasi Undang Undang Perseroan Terbatas : Upaya Membuka Tanggung Jawab Pribadi Pemegang Saham Perseroan Terbatas di Indonesia - Wardhani, Adelia Kusuma (Kertha Patrika, 2024)
Indonesia has Law No. 40/2007 on Limited Liability Companies which regulates the personal liability of shareholders, also known as the Piercing the Corporate Veil doctrine. Unfortunately, the provisions regarding personal liability for shareholders are not well applied by the courts. This study aims to investigate the weakness of the application of personal liability of shareholders by the Courts in Indonesia based on the benchmarks in Article 3 paragraph (2) of the Limited Liability Company Law. This research uses a normative approach, based on legislation and jurisprudence. The results of this study indicate that there are inconsistencies in the application of personal liability for limited liability company shareholders by the Indonesian Courts due to unclear indicators of personal liability. The United Kingdom is one of the countries that applies personal liability of shareholders consistently by the Court. The indicators owned by the UK can be a reference for Indonesia to reform Article 3 paragraph (2) of the Limited Liability Company Law. This aims to ensure that third parties receive legal protection from the application of personal liability of limited liability company shareholders.